PENDEKATAN PENELITIAN KORELASIONAL: KONSEP, METODE, DAN APLIKASINYA - Andi Iting; Syarifuddin Ondeng; Muh. Khalifah Mustami (Jurnal Panrita, 2024)
The purpose of this study is to understand the concept of correlational research. Correlational research is a type of study aimed at identifying the relationship between two or more variables and measuring the strength and direction of that relationship. It is a quantitative research method designed to identify relationships between variables without altering or manipulating them. In correlational research, researchers focus on measuring the degree of relationship or association between existing variables. This research does not attempt to establish causation but rather examines whether significant correlations exist between the variables studied. The method used in this research involves a literature review, where the researcher examines related literature and relevant sources. The findings conclude that an appropriate research design can utilize either a cross-sectional design (collecting data at a single point in time) or a longitudinal design (collecting data at multiple points in time). Reliable and valid instruments, such as questionnaires, surveys, or secondary data, are employed to measure the variables. The collected data are quantitative and are analyzed statistically. Statistical analysis techniques, such as Pearson or Spearman correlation coefficients, can be used to measure the strength and direction of the relationship between variables. Correlational research is highly useful in providing insights into relationships between variables and can serve as a foundation for further studies.